2020
DOI: 10.31234/osf.io/3qg9p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlates of anxiety and depression in frontline healthcare workers treating people with COVID-19 in Bangladesh

Abstract: Background: Healthcare workers (HCWs) who are in the frontline during the COVID-19 pandemic are often under significant pressures which may predispose them to mental ill-health. This study aimed to investigate the prevalence of anxiety and depression among HCWs and factors correlated with mental problems during the COVID-19 pandemic in Bangladesh.Methods: A cross-sectional survey was conducted between July and August 2020. A self-reported online questionnaire was utilized to collect data. The survey included q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 43 publications
6
46
0
Order By: Relevance
“…The extent to which the findings might relate to longer sleep of poorer quality given crowded living situations or other factors warrants additional study. The present findings also linked smoking to depression, consistent with prior reports in Bangladesh (Islam et al, 2020e;Tasnim et al, 2020) and global findings from 48 low-and middle-income countries (Stubbs et al, 2018) and a systematic review (Fluharty et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The extent to which the findings might relate to longer sleep of poorer quality given crowded living situations or other factors warrants additional study. The present findings also linked smoking to depression, consistent with prior reports in Bangladesh (Islam et al, 2020e;Tasnim et al, 2020) and global findings from 48 low-and middle-income countries (Stubbs et al, 2018) and a systematic review (Fluharty et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…A pre-tested semi-structured questionnaire adapted from the literature [10] was used to collect data using the Google survey tool. The questionnaire was translated using the guidelines of back translation (e.g., Beaton et al (2000)) [35], as previously used in Bangladesh [25,36,37]. The questionnaire was translated into Bangla (participants' first language) and then translated back to English by experts with very good command of both the Bangla and English languages.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The total score was calculated by summing the raw scores of each item ranging from 0-27, with a higher score indicating greater severity of depression. The levels of depressive symptoms were classified into five groups according to their score as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27). In the present study, the PHQ-9 scale was found to have Cronbach's α of 0.86.…”
Section: Patient Health Questionnaire (Phq-9) Scalementioning
confidence: 99%
See 2 more Smart Citations